Penurunan Viabilitas dan Ekspresi Gen Virulensi Salmonella Typhimurium Akibat Paparan Ekstrak Air Bawang Putih - Tiara, Andani; Nurjanah, Siti; Wulandari, Zakiah (Jurnal Teknologi dan Industri Pangan, 2025)
Garlic contains antibacterial compounds that are heat-sensitive. The ultrasonic bath method can reduce extraction time and oxidative degradation during aqueous garlic extraction, enhancing its antibacterial properties. Salmonella Typhimurium, a common bacterial contaminant in chicken, can cause salmonellosis in humans by expressing specific virulence genes. This study examined the reduction in the expression of S. Typhimurium virulence genes (stm, invA, stn, and pefA) after exposure to aqueous garlic extract. Freeze-dried garlic was dissolved in several concentrations (5, 10, 20, 40, and 80 mg/mL distilled water) and sonicated using an ultrasonic bath for 5, 10, and 20 min. Total phenolic content of each extract was measured, and the minimum bactericidal, minimum inhibitory, and sub-inhibitory concentrations against S. Typhimurium were also determined. Virulence gene expression was measured by reverse transcription q-PCR. The extract prepared at 80 mg/mL for 20 min showed a higher phenolic content (366.57 mg GAE/100 g) and inhibition zone (19 mm). MBC, MIC, and SIC concentrations were 80, 40, and 20 mg/mL. S. Typhimurium exposed by MIC and SIC for 2 h reduced the number (1.39 and 1.22 log reduction CFU/mL) and down-regulated the expression genes (stm, invA, stn, and pefA). The higher reduction of expression genes was observed for invA (0.98 and 0.75 log reduction) relative to the 16s rRNA housekeeping gene. These results suggest that the aqueous garlic extracts reduce the bacterial count and the virulence of S. Typhimurium.